Althea : the life of tennis champion Althea Gibson - Jacobs, Sally H., 1957- (St. Martin's Press, 2023)
"A captivating book that brilliantly reveals an American sports legend long overlooked. Sally Jacobs tells the riveting story of Althea Gibson, my personal hero, who overcame daunting odds - on the tennis court and off - to stand at the world pinnacle of her sport and became an inspiration to many." - Billie Jean King In 1950, three years after Jackie Robinson first walked onto the diamond at Ebbets Field, the all-white, upper-crust US Lawn Tennis Association opened its door just a crack to receive a powerhouse player who would integrate "the game of royalty." The player was a street-savvy young Black woman from Harlem named Althea Gibson who was about as out-of-place in that rarefied and intolerant world as any aspiring tennis champion could be. Her tattered jeans and short-cropped hair drew stares from everyone who watched her play, but her astonishing performance on the court soon eclipsed the negative feelings being cast her way as she eventually became one of the greatest American tennis champions. Gibson had a stunning career. Raised in New York and trained by a pair of tennis-playing doctors in the South, Gibson's immense talent on the court opened the door for her to compete around the world. She won top prizes at Wimbledon and Forest Hills time and time again. The young woman underestimated by so many wound up shaking hands with Queen Elizabeth II, being driven up Broadway in a snowstorm of ticker tape, and ultimately became the first Black woman to appear on the cover of Sports Illustrated and the second to appear on the cover of Time. In a crowning achievement, Althea Gibson became the No. One ranked female tennis player in the world for both 1957 and 1958. Seven years later she broke the color barrier again where she became the first Black woman to join the Ladies Professional Golf Association (LPGA). In Althea, prize-winning former Boston Globe reporter Sally H. Jacobs tells the heart-rending story of this pioneer, a remarkable woman who was a trailblazer, a champion, and one of the most remarkable Americans of the twentieth century"--